2013
DOI: 10.1063/1.4815943
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent dynamics transition of intermittent plastic flow in a metallic glass. I. Experimental investigations

Abstract: Cooling shrinkage can increase the atomic packing density of metallic glasses, which can influence their elastic and plastic behaviour. In the present study, the compressive deformation behaviour of a Zr-based metallic glass at temperatures well below the glassy transition temperature, say 123 K to room temperature, is experimentally revealed. The elastic modulus and the shear modulus at different temperatures are measured to elucidate the yield strength changes with temperature according to the model of shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
(43 reference statements)
2
13
0
Order By: Relevance
“…Therefore, it is required to uncover the correlation between the strength and the fracture behaviors of BMGs under different temperatures, and loading rates. Abundant researches have been carried out to explore the influence of cryogenic temperature on the strength and the plastic behavior (serrated flow) of BMGs in the past several years5910111213. The quasi-static deformation tests as well as the dynamic deformation tests of many BMGs also were performed, which suggested a negative-sensitivity of strength to strain rate681415161718192021.…”
mentioning
confidence: 99%
“…Therefore, it is required to uncover the correlation between the strength and the fracture behaviors of BMGs under different temperatures, and loading rates. Abundant researches have been carried out to explore the influence of cryogenic temperature on the strength and the plastic behavior (serrated flow) of BMGs in the past several years5910111213. The quasi-static deformation tests as well as the dynamic deformation tests of many BMGs also were performed, which suggested a negative-sensitivity of strength to strain rate681415161718192021.…”
mentioning
confidence: 99%
“…Once the shear band is formed, an elastic-strain field can appear in the front of the shear-band tip, which is analogy to the elastic-strain field in the front of the crack tip. The size of the elastic-strain field is several times larger than the inter-spacing between two neighboring shear bands (Liu et al, 2013a), which causes the overlap of two elastic-strain fields initiated from neighboring shear bands. The overlap of the elastic-strain field can result in a hierarchy of length scales (Bharathi et al, 2001), leading to a self-organized critical behavior that is manifested as a scaling behavior of the shear-avalanche statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic-emission experiments have clearly shown that the dynamic behavior of the shear-avalanche can be associated with the elementary mechanisms of energy dissipation (Klaumünzer et al, 2011a;Kumar and Ananthakrishna, 2011;Koslowski et al, 2004;Dimiduk et al, 2006). This energy relaxation duration is significantly affected by the environmental temperature (Klaumünzer et al, 2011b), strain rate (Liu et al, 2013a;Ren et al, 2011), and outside geometric confinement (Wang et al, 2009), which can modify the dynamic behavior of metallic glasses. From this point, a crucial question is raised: how does the dynamics of the intermittent deformation change, when this jerky flow is disturbed, and how does then the plastic deformability of metallic glasses change?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Figure 3, the K Q value decreases approximately 43% when the temperature is decreased from 298 to 123 K. In the meantime, the decrease in the temperature causes the yield strength of the MG to increase roughly 20% [36]. Therefore, the R value at 298 K is almost 4.4 times larger than the value at 123 K. The increased γ value and the reduced r H value with the decreasing temperature suggests that the softening behavior is weakened, which is the main reason causing the difference in the fracture surfaces generated at different temperatures.…”
Section: Discussionmentioning
confidence: 99%